PENGAMATAN UNSUR GEOKIMIA BATUAN ULTRAMAFIK DI DAERAH PERTAMBANGAN PT. BINTANG DELAPAN MINERAL - Supit, Jance Murdjani; Asy’ari, Muhammad Amril (POROS TEKNIK, 2013)
The research is dealing with weathering and geochemistry behavior of ultramafic rock element. This study consists of field work and laboratory analysis The aim of research is to understand the grade of weathering, and geochemistry behavior of element during weathering in Bahodopi, Morowali Regency, Central sulawesi. Red limonite, yellow limo-nite, and saprolite are the weathering product of ultramafic rock (peridotite). Weathering index calculation indicates the weatering grade increasing with the depth decreasing (from 12 metres to 0 metre or from bedrock to red limonite). The mass balance calculati-on indicates the addition of Ni grade increases up to 315% (10.054 kg/m3), Fe = 286% (180.765 kg/m3), Co = 243% (986kg/m3), Al = 340% (8,923 kg/m3), Cr = 144% (1,303 kg/m3), whereas Mg grade decrease up to 99% (158kg/m3), Si also has 99% (188 kg/m3).